Development of a Software Based Telematic Gateway - Türkten,Batuhan (2025)
Telematics units are widely spreading in the automotive industry. Getting realtime data from the systems is essential for creating services in the back office which builds value for both companies and end customers. The services created greatly impact maintenance strategies, future developments, and keeping the vehicle more sustainable and secure for both end users and customers. However, adding new hardware for this purpose is not always an easy option for companies that collaborate with different corporations and do not build the final product. To solve this issue a software model can be generated that will perform the features of a telematic unit which will help to reduce unnecessary hardware in the system and improve the installation process of products. This master’s thesis report presents an investigation into developing a softwarebased telematic unit called Software Agent. This investigation splits mainly 3 areas which are deciding the necessary features to be performed, deciding the host hardware for the software component, and ensuring the data security according to the decided design. The features that were implemented were decided based on the responsibilities of a standard telematics unit like data storing, filtering, and providing secure storage for the keys also decided according to the potential services for the company like data buffer and diagnostic trigger. For deciding the host of the Software Agent 4 different solutions have been created. A comparison has been made on these 4 different solutions and host hardware decided according to the assignments. These assignments are created based on companies needs and feasibility of the system. The last part of the investigation is data security which is established by an encryption method. Three different encryption methods have been compared based on performance and memory usage and the most advantageous one is integrated into the Software Agent for fulfilling the data security. After these investigations, a test system was created using suitable hardware like Arduino, Raspberry Pi, and MCP2515 module. Using this test system data have been collected and sent to the database for visualization. At the end of the testing phase results show that with the solution that has been decided necessary features can be performed in the system by using fewer hardware resources and ensuring data security.
Keywords: Telematics; CAN